The Role of Character Education in Reducing Bullying Behaviour in Elementary Schools - Darmayanti, Dyan Paramitha; Henri (Celebes Journal of Elementary Education, 2024)
The phenomenon of bullying in elementary schools is an important issue that affects students' psychological and social development. This study aims to identify the forms of bullying in elementary schools and explore the role of character education in reducing bullying behaviour. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews and participatory observation involving six informants, namely three teachers, two students and one parent. The results showed that bullying that occurs in elementary schools is more often in the form of verbal and social bullying, with a significant impact on the victim's self-confidence and academic achievement. Character education that includes the values of empathy, tolerance and mutual respect is implemented in the school curriculum and extracurricular activities as a preventive effort. However, the implementation of character education is still faced with challenges, such as the mismatch between the values taught at school and the application at home. This study suggests that character education should be implemented consistently and involve cooperation between teachers, parents and the community to create a bullying-free environment.